Inovasi Produk UMKM Dari Limbah Elektronik: Studi Potensi dan Kelayakan - Haeruddin Haeruddin; sudirman sudirman; Imran Tahalua (Al-Buhuts, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy but continue to face challenges in achieving sustainable business development, particularly in utilizing the growing volume of electronic waste (e-waste). This study aims to analyze the potential use of e-waste as a source of product innovation and to assess the business feasibility of circular economy based MSMEs in South Sulawesi. The research adopts a mixed-method approach using an exploratory sequential design, emphasizing qualitative methods through field observations, in-depth interviews, and focus group discussions, supported by descriptive quantitative analysis using SWOT and Cost Volume Profit (CVP) analysis. The findings indicate that MSMEs possess adequate basic technical skills to develop recycled products, particularly electric fans made from e-waste components. The availability of local raw materials and relatively low production costs are identified as the main strengths of the business. CVP analysis shows that the break-even point is approximately 22 units per month, indicating a relatively low financial risk. Overall, the recycled electric fan business is considered technically, market-wise, and financially feasible, and has the potential to support MSME empowerment and strengthen the implementation of the circular economy at the local level.